2005
DOI: 10.1038/sj.eye.6702056
|View full text |Cite
|
Sign up to set email alerts
|

Second eye of patients with unilateral neovascular age-related macular degeneration: Caucasians vs Chinese

Abstract: Purpose To investigate the correlation between morphological features of choroidal neovascularisation (CNV) secondary to agerelated macular degeneration (AMD) in the first eye and the severity of age-related maculopathy (ARM) in the fellow eyes in two racial groups: Caucasians and Chinese. Participants A total of 135, fluorescein angiograms of patients with unilateral neovascular AMD and ARM in the fellow eyes were included in the study: 38 Caucasians from King's College Hospital, UK; 45 Caucasians from West K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The exudative form is the leading cause of irreversible vision loss in subjects over 65 years of age living in economically developed countries and accounts for >80% of cases of legal blindness associated with the disease [57]. Risk estimation is crucial in order to provide adequate patient monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The exudative form is the leading cause of irreversible vision loss in subjects over 65 years of age living in economically developed countries and accounts for >80% of cases of legal blindness associated with the disease [57]. Risk estimation is crucial in order to provide adequate patient monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Abugreen et al [21] found that the fellow eyes of occult CNV have significantly more severe AMD features compared to eyes with classic CNV. Similarly, Sivaprasad et al [23] showed that this kind of association between the CNV type in the affected eye and the severity of the disease in the fellow eye can only be applied on Caucasians, compared to Chinese patients who did not show a similar disease pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The drusen load findings of our study support findings reported previously in the literature. It has been reported that the clinical features in the fellow eye correlate with the type of CNV in the affected eye in AMD patients with unilateral CNV using colour fundus photography [21,23]. Abugreen et al [21] found that the fellow eyes of occult CNV have significantly more severe AMD features compared to eyes with classic CNV.…”
Section: Discussionmentioning
confidence: 99%